Analisis Penokohan Pada Novel Edensor Karya Andrea Hirata Sebagai Alternatif Bahan Pembelajaran Unsur Penokohan - Listiyani, Tiya; Wardana, Deni; Widjojoko, Widjojoko (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Learning materials in the learning process are very important. Learning materials commonly used in the material of the elements of characterization, especially grade IV elementary school using learning materials obtained from teacher and student books and the internet. This characterization is contained in indonesian material class IV Elementary School, theme 4 sub-theme 1 and 2, In the material there is an element of characterization in the form of character protagonist and antagonist as well as main and additional characters. To add insight into the elements of teacher characterization can use novels. One of the novels used is the novel Edensor by Andrea Hirata. The purpose of this study is to analyze the novel as an alternative learning material for the characterization element of the story. In this research process researchers use qualitative research approaches, with content analysis methods and data collection techniques through documentation. The results of the research obtained are the characterization element in the form of additional main characters, as well as the character of the characterization of a number of 44 pieces that show the character of the character. 37 pieces that show the protagonist. and 7 pieces that show the character of the antagonistic character. The characterization of the novel is presented through expository techniques and dramatic techniques. From the results of the analysis, researchers will develop learning materials in the form of handouts and student worksheets